2013
DOI: 10.4132/koreanjpathol.2013.47.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Findings of the Micropapillary Variant of Urothelial Carcinoma: A Comparison with Typical High-Grade Urothelial Carcinoma

Abstract: BackgroundMicropapillary variant of urothelial carcinoma (MPUC) showed distinct pathologic features and aggressive behavior. The cytologic findings of MPUC are still indistinct. In this study, we evaluated the cytological findings of MPUC compared with those of high-grade urothelial carcinoma (HGUC).MethodsThe voided urine cytology of 8 cases of MPUC and 8 cases of HGUC was reviewed. Following cytological parameters were evaluated: cellularity, background, number of small, tight papillary clusters, small acina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…16 Urine cytology specimens usually exhibit micropapillae without fibrovascular cores and an acini-like architecture with scalloped outer contours. 4 In the present case, intraperitoneal spread of disease was present and these tumor cells were histologically Diagnostic Cytopathology DOI 10.1002/dc identified as plasmacytoid UC. 10 Compared to that of typical high-grade UC, the cytology of micropapillary UC shows a large number of small, tight papillary clusters, small acinar structure, fewer isolated cells, and hyperchromatic nuclei.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…16 Urine cytology specimens usually exhibit micropapillae without fibrovascular cores and an acini-like architecture with scalloped outer contours. 4 In the present case, intraperitoneal spread of disease was present and these tumor cells were histologically Diagnostic Cytopathology DOI 10.1002/dc identified as plasmacytoid UC. 10 Compared to that of typical high-grade UC, the cytology of micropapillary UC shows a large number of small, tight papillary clusters, small acinar structure, fewer isolated cells, and hyperchromatic nuclei.…”
Section: Discussionmentioning
confidence: 50%
“…The majority of tumors are found to invade muscle at the time of presentation, and lymphovascular invasion is present in more than half of muscle-invading micropapillary UCs. 4 Cytologic features such as cellularity, dense or vacuolated cytoplasm, moderate to severe nuclear pleomorphism, irregular nuclear membranes, coarse granular chromatin, and small and prominent nucleoli are not helpful for distinguishing micropapillary UC from typical high-grade UC. 14 The overall outline of the cell papillae or nests was very irregular and the papillae or nests consisted of highly pleomorphic, atypical cancer cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Micropapillary UC (MPUC) has an aggressive clinical course with early nodal/distant metastasis, which may alert the clinician. [11] Some investigators have suggested using p63, p40, and GATA-binding protein 3 immunohistochemistry for differentiating MPUC from typical UC. [12]…”
Section: Discussionmentioning
confidence: 99%